The Effectiveness Of The Role of The Special Job Fair SMK SMTI Banda Aceh in Enhancing Graduates Employability to The Business/Industry World - Zulkifli Salman Gea; Teuku Zulyadi; Nurfahmi Nurfahmi (Ar-Raniry State Islamic University, Indonesia, 2022)
This study aims to see the effectiveness of the role of the Special Job Fair at SMK SMTI Banda Aceh in enhancing graduates employability to the Business/Industry World. This study uses a qualitative method by conducting interviews with the Industrial Relations Team and Alumni of SMK SMTI Banda Aceh and the Special Job Exchange Unit of SMK SMTI Banda Aceh with a focus on graduate data from 2016 to 2021 which includes the total number of graduates and the number of graduates working in The Business/Industry World, the graduates who are entrepreneurs, and the graduates who continue their education. The results showed that the role of the Special Job Fair SMK SMTI Banda Aceh in marketing graduates to The Business and Industrial was effective. This can be seen from the number of graduates who work and are being an entrepreneur,is increasing every year except for 2021. In 2021, there is a decrease in the number of graduates who work due to the COVID-19 pandemic situation. Many Special Job Fair program activities cannot be implemented due to efforts to overcome the covid-19 pandemic which has an impact on the distribution of graduates to The Business/Industry World.